The Implication of Asbabun Nuzul for Al-Quran Verses Interpretation - Khairunnas Jamal; Arif Iman Mauliddin; Derhana Bulan Dalimunthe (Kawanua International Journal of Multicultural Studies, 2022)
This article aims to explore the existence of asbabun nuzul for the interpretation of Al Quran verses. The mufassir admits that without asbabun nuzul it will be difficult to understand the verses of the Qur'an. Therefore, this study reveals the implication of asbabun nuzul for interpretation. This article raises the issue of child's lineage to the ones who are the un-biological father. This study is library research by using articles and books as the primary sources. The results of this study show that asbabun nuzul has the primary authority in the interpretation such as clarifying the understanding of the process of legal determination, reviewing the specificity of the law, and rejecting the existence of hasr (legal restrictions) in the verses that contains legal barriers.